Analisis de eficiencia de la Planta de tratamiento de Aguas Residuales, Rumipamba de las Rosas, cantón Salcedo, Provincia de Cotopaxi, periodo 2018. - León Cortéz, Jhosua Sebastián (2019)
The purpose of the project was to characterize the general efficiency of the Rumipamba de las Rosas wastewater treatment factory in Salcedo canton, to propose aid measures for the impacts generated. This was developed as a result of the fact that the areas around the plant discharge their water to the treatment plant. In order to justify this objective, certain activities were carried out, such as: the respective characterization of wastewater at two sampling points at entry and exit, complying with the established protocol. Next, the general efficiency of the factory was determined, which is 45.75%, being a low percentage, due to the fact that certain parameters such as: fecal coliforms exceed the permissible limits of the current regulations and others such as: sulphates and total solids, its efficiency is low. To complete this project, the most appropriate proposals for the implementation of the factory were calculated. In order to comply with this, an inflow of the incoming flow was made for a future population within 25 years. Once the design flow was obtained, the remediation measures were developed, such as: 3 slow sand filters that will allow to retain the solids, improve color and remove fecal coliforms present in the wastewater, in the same way a chlorination chamber to oxidize inorganic matter and disinfect the water to carry out direct discharges to the Cutuchi River. After the research project was delivered to the Department of potable water and sewerage of the GAD Municipal canton Salcedo to make the immediate implementation of the proposed measures that will increase the overall efficiency of the plant is expected to be 90.41% increasing the efficiency in 44.66%, at the same time a removal of (90.75 MPN / 100ml) of fecal coliforms (8.1mg / l) of sulfates (84.4mg / l) of total solids is expected, complying with as stipulated in Ministerial Agreement 097, Annex 1, Table 9. Limits of Discharge to a Body of Fresh Water.